The Effect of Instagram Social Media Attraction, Service Quality, And Brand Image On Repurchase Intention of Po. Gunung Harta Customers - Mohamad Zhidan Izzul Arobi; Ni Made Rastini (International Forum of Researchers and Lecturers, 2025)
Repurchase intention is the consumer’s tendency to purchase a brand or take an action related to the intention of repurchasing a product that has been purchased in the past and to engage in repeated purchases in the future. This study aims to analyze the effect of Instagram social media attraction, service quality, and brand image on repurchase intention. The study used a sample of 100 PO. Gunung Harta customers who had used the company’s services at least twice within one year. The research was conducted at the head office of PO. Gunung Harta located in Denpasar City. The method applied in this study was a survey method using questionnaires and interviews, with inferential statistical analysis through multiple linear regression. The results indicate that Instagram social media attraction has a positive and significant effect on repurchase intention. Service quality has a positive and significant effect on repurchase intention. Brand image also has a positive and significant effect on repurchase intention. This study is expected to serve as a reference for future researchers. These factors are interconnected, and their collective influence on repurchase intention highlights the importance of a well-rounded marketing strategy that incorporates social media engagement, superior service quality, and a strong brand image. Future research could explore the impact of additional factors, such as customer loyalty programs or word-of-mouth, to gain deeper insights into consumer repurchase behavior.